DRIVING EDUCATIONAL INNOVATION THROUGH COLLABORATIVE LEARNING MODELS - Putri Mahanani (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2023)
In the rapidly evolving landscape of education, traditional teaching approaches are increasingly inadequate for preparing students with the skills required in the 21st century. Collaborative learning models have emerged as a vital strategy to drive educational innovation by fostering active engagement, critical thinking, and the development of essential interpersonal skills. This paper explores the theoretical foundations, practical applications, and challenges of implementing collaborative learning across diverse educational settings. Findings indicate that collaborative learning not only enhances academic achievement but also transforms the role of educators and integrates effectively with digital technologies to expand learning opportunities. Despite challenges such as unequal participation and technological barriers, best practices including structured tasks and reflective assessment contribute to successful outcomes. Ultimately, collaborative learning offers a powerful framework for creating more inclusive, relevant, and future-ready educational experiences.